Academic Corruption in the Universities of the Kurdistan Region – Iraq A Field Study from the Perspective of Faculty Members - محمد, ميران محمد صالح (Sulaimani Journal for Humanities, 2025)
The study aimed to identify the opinions of a sample of faculty members in public universities in the Kurdistan region - Iraq about scientific corruption, its signs and sources, and to identify its types, objectives, factors and fields, and ways to limit its spread. This study is considered one of the descriptive studies that rely on collecting, analyzing, and interpreting facts to extract their significance, through the use of a social survey approach using the sample method, as a questionnaire was applied to a random sample consisting of (300) male and female teaching staff who were selected from faculty members in public universities in the Kurdistan Region. Iraq. The study reached several results, including: The phenomenon of scientific corruption exists in society in varying forms, and the cause of corruption is due to a group of factors represented by society’s deviation from noble values, morals, and character traits, partisan interference, and the presence of intermediaries and favoritism. In addition to the lack of legal accountability.
Keywords: Corruption Academic Corruption Higher Education University Faculty